Antimicrobial resistance patterns in a Port Elizabeth hospital - Meiring, Jillian A (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1993)
Antibiotic resistance in clinical bacterial isolates remains an ongoing problem requiring continuous monitoring to effect some form of control. Comparative studies have not been previously reported for the Eastern Cape Region, South Africa and this study was undertaken to monitor resistance patterns in clinical isolates from Provincial Hospital, Port Elizabeth. Over the three year period 1989 to 1991, 9888 susceptibility results from isolates examined in the SAIMR pathology laboratory were analysed and collated using a stand-alone computer program. Resistance patterns for a range of nineteen antibiotics were collated for isolates from various sampling points within the hospital. Results were reported as resistance patterns in individually isolated species. Levels of resistance in each species were compared to those reported from South Africa and abroad, and changing patterns of resistance were noted within the three year period at the Provincial Hospital, Port Elizabeth.
Keywords: Antibiotics; Drug resistance in microorganisms; Hospitals -- Drug distribution systems -- South Africa -- Port Elizabeth